MOBILIZATION OF LOCAL SAMPLES OF VEGETABLE CROPS, CUCURBITS AND LEGUMINOUS CROPS DURING THE EXPEDITION TO THE REPUBLIC OF ARMENIA IN 2017 - A. M. Artemyeva; S. S. Abremskaya (Труды по прикладной ботанике, генетике и селекции)
In 2017, an expedition was conducted in the Republic of Armenia. Its purpose was to collect local samples of vegetable crops, cucurbits and leguminous crops. The mission of the expedition was to study the seed assortment in markets, agricultural stores, farm fields, and a territorial survey of a number of districts in the Republic in accordance with the developed route. It was found out that common bean, tomato, onion, sweet pepper and hot pepper, spicy-flavored crops and cucurbits are widely used by the local population. Farmers were observed to have a wide diversity of crop varieties derived from their own seeds. As a result, 415 samples were collected and delivered to VIR, including 280 samples of vegetable crops (tomato, onion, coriander, dill, basil, radish, cucumber, sweet pepper, etc.), 70 of leguminous crops (common bean, etc.), 37 of cucurbits, 14 of oil and fiber crops, 12 of wild species, and 2 of alfalfa (one of them wild). Among fruit-bearing vegetable crops and cucurbits there are sources of valuable traits, such as ornamentality, productivity, resistance to abiotic and biotic stressors in the challenging climate conditions of the Republic of Armenia.